CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

Effect of sCD83 on direct allosensitization after corneal transplantation - Schoenberg, Alfrun Patricia; Peckert-Maier, Katrin; Hadrian, Karina; Hamdorf, Matthias; Cursiefen, Claus; Zinser, Elisabeth; Bock, Felix (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Pre-incubation of corneal donor tissue with soluble CD83 improves graft survival via the induction of pro-resolving macrophages - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert, Katrin; Wild, Andreas; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces the resolution of inflammation in an antigen-induced arthritis (AIA) model. Joint swelling and the arthritis-related expression levels of IL-1 beta, IL-6, RANKL, MMP9, and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP(+) osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell-specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as Oc-Stamp, Mmp9 and Nfatc1, Ctsk, and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g., Mrc1/2, Marco, Klf4, and Mertk, were upregulated. Interestingly, members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were also highly induced by sCD83 in samples derived from RA patients. Finally, we elucidated the sCD83-induced signaling cascade downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signaling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce the resolution of inflammation and to prevent bone erosion in autoimmune arthritis.
CRIS-Team WoS Importer:2022-09-09